PENGARUH SARANA PRASARANA PRAKTIKUM DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR SISWA TEKNIK KENDARAAN RINGAN OTOMOTIF SEKOTA GORONTALO - Pramudibyo, Sugeng; Arafat, Muh. Yasser; Nasaru, Muhamad Sidik (Program Studi Pendidikan Teknik Mesin, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Palangka Raya, 2025)
Vocational High Schools (SMK) are mandated by law to prepare human resources who are ready to enter the world of work and become a productive workforce, but this has not been optimal in preparing students for careers. The number of unemployed in this case indicates that the percentage of unemployed vocational school graduates is still relatively high. One of the ways education plays a role in reducing unemployment is by improving the quality of education. One factor that can improve the quality of education is improving learning facilities and infrastructure. Facilities and infrastructure in the educational process are included as one of the standards of the school or educational agency concerned. This research aims to analyze: (1) the influence of infrastructure on learning outcomes, (2) the influence of motivation on learning outcomes, (3) the influence of infrastructure and motivation simultaneously on learning outcomes. This research is quantitative research carried out at the Automotive Light Vehicle Engineering Vocational School in the city of Gorontalo. The population in this study was 72 students. The type of questionnaire in this research is a closed questionnaire and the results are analyzed using simple linear regression analysis and multiple linear regression analysis. The results of this research are: (1) Practical facilities and infrastructure have a significant impact on student learning outcomes at the Automotive Light Vehicle Engineering Vocational School by 31.8%. (2) Learning Motivation has a significant effect on the Learning Outcomes of Automotive Light Vehicle Vocational School students by 41.2%. (3) Practical Infrastructure and Learning Motivation simultaneously have a significant effect on the Learning Outcomes of Automotive Light Vehicle Vocational School students by 50.6%.